PP.17.01: WHITE-COAT EFFECT CAUSES OVERESTIMATION OF DIURNAL AND 24 HOURS BLOOD PRESSURE VALUES ON AMBULATORY BLOOD PRESSURE MONITORING. (June 2015) - Salvo, F.; Lonati, C.; Morganti, A.
Abstract : Objective: In patients (pts) undergoing ambulatory blood pressure monitoring (ABPM) initial and final values of blood pressure (BP) are often markedly higher than those recorded throughout the rest of ABPM, a finding that resembles the white-coat effect (WCE) phenomenon observed with clinical measurement of BP. Design and method: Analysis was carried out in 321 ABPM (M/F 113/208) in which WCE was identified by the first measured value of BP being at least 10 mmHg greater than mean diurnal systolic blood pressure (mDSBP). mDSBP and mean 24 hours systolic BP (m24hSBP) were calculated with and without the inclusion of the first two hours and the last hour of recording (WCE window, WCEw). The magnitude of WCE (WCEm) was also examined as mSBP of WCEw values whereas WCE duration (WCEd) was calculated multiplying the number of SBP values >10 mmHg higher than mDSBP by the time interval between recordings. The same analysis was repeated gender based and in a subset of 89 ABPM (M/F 30/59) from pts on treatment with beta-blockers (BB). Results: Excluding WCEw values, mDSBP and m24hSBP fell respectively from 134 ± 1 to 131 ± 1 mmHg and from 130 ± 1 to 128 ± 1 mmHg (p < 0.01 for both) while the rate of mDSBP and m24hSBP above the conventional limits of normalcy decreased respectively from 45% to 33% and from 49% to 40%. As a result, considering both measurements, 16% of patients had a false diagnosis of hypertension. After the subtraction of WCEw values the reductions in mDSBP and m24hSBP were similar in both genders, as well as WCEm (145 ± 1 mmHg) whereas WCEd was longer in females (68 ± 2 vs 58 ± 2 minutes, p < 0.01). A shorter WCEd was found in pts on BB with respect to those not in treatment with these medications (58 ± 3 vs 67 ± 2 minutes, p < 0.01). Conclusions: In both genders inclusion of WCEw values significantly increases mDSBP and m24hSBP augmenting the number of incorrect diagnosis of hypertension. Among females WCEd is longer than in males and, overall, it is reduced by BB.